2019
DOI: 10.5194/bg-2019-358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adult life strategy affects distribution patterns in abyssal isopods – implications for conservation in Pacific nodule areas

Abstract: <p><strong>Abstract.</strong> Aim of our study is to gain a better knowledge about the isopod crustacean fauna of the abyssal Clarion Clipperton Fracture Zone (CCZ) located in the central Pacific Ocean. In total, we examined 22 EBS samples taken at 6 abyssal areas in the central pacific manganese nodule area (CCZ and DISCOL). The dataset comprised 619 specimens belonging to 187 species of four different isopod families: 91 species (48.6 % of total) belong… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Understanding the diversity of seafloor habitats and the associated fauna is critical to making informed decisions about deep-sea conservation (Brix et al, 2019;McQuaid et al, 2020;Jones et al, 2021;Washburn et al, 2021). In the CCZ, the possible extraction of the abundant and valuable nodules could not only result in loss of substratum but will also result in seabed upheaval and possible biodiversity loss, and perhaps an ongoing effect on the (Ratnasingham and Hebert, 2013) local food web (Levin et al, 2016;Niner et al, 2018;Brix et al, 2019;Simon-Lledóet al, 2019a; (E-G). ab, abradial; ASA, arm spine articulation; dis, distal; PSA, parasol spine articulation.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the diversity of seafloor habitats and the associated fauna is critical to making informed decisions about deep-sea conservation (Brix et al, 2019;McQuaid et al, 2020;Jones et al, 2021;Washburn et al, 2021). In the CCZ, the possible extraction of the abundant and valuable nodules could not only result in loss of substratum but will also result in seabed upheaval and possible biodiversity loss, and perhaps an ongoing effect on the (Ratnasingham and Hebert, 2013) local food web (Levin et al, 2016;Niner et al, 2018;Brix et al, 2019;Simon-Lledóet al, 2019a; (E-G). ab, abradial; ASA, arm spine articulation; dis, distal; PSA, parasol spine articulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies that have sought to describe the benthic fauna that typify the CCZ have also revealed extraordinarily high taxonomic diversity across representatives from all Domains of Life (e.g. Amon et al, 2016; De Smet et al, 2017; Shulse et al, 2017; Wilson, 2017; Hauquier et al, 2018; Goineau and Gooday, 2019; Brix et al, 2020; Christodoulou et al, 2020), making the CCZ of critical importance for biodiversity conservation. In many of these studies, data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…species-abundance curves) strongly suggest that many – arguably most – species remain unaccounted for, with high species turnover over relatively short spatial scales even in groups that are brooders like Isopoda (e.g. Wilson, 2017, Brix et al, 2020). Remoteness of habitat and spatial variability in species composition of this sort present challenges for performing robust ecological studies, as evidenced by the scarcity of ecologically meaningful data available for even the most conspicuous ‘common’ epifaunal species in the CCZ (Danovaro et al, 2017), including many echinoderm species (Amon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%